(3GdESJQGJjLqjI GdOaGYqjI GdJQcjI aj YgO GdQFjS CQOhZGfs - (3PjGH(B, (3eMeO CMeOs ((3YeGf(B;(3YeGfs (3OGQ CeLO ddfTQ h GdJhRjY (B;(3EHUGQ fGTQhf h ehRYhfs, 2022)
(3JdLC GdOhd GdJj dG jchf eYjGQ GdbhI dUGdMgG Edi GJNGP JOGHjQ GSJKfGFjI hbGFjI dJYRjR bOQGJgG GdYScQjI hGfJgGL Sdhc jJYGed eY GdeJZjQGJ HHQGZeGJjI, HeG Cf JQcjG JJhGLO aj efWbg gTg CefjkG JYGfj ef UQGYGJ ddbhi GdYXei hJTgO NdGaGJ hMQhH eYbOI hNGUI GdLhGQ GdEbdjej GdJQcj GdPj jSHH JgOjO ddCef Gdbhej eeG OaY HUGfY GdbQGQ Edi EYOGO GSJQGJjLjI OaGYjI GSJLGHI ddeJZjQGJ GdJj WQCJ ef CLd GdOaGY Yf OhQ hecGfI JQcjG, hMaGXkG Ydi GdJhGRf GdEbdjej dG SjeG HYO CMOGK GdQHjY GdYQHj EP TgOJ GdefWbI JZjQkG MbjbjkG Ydi UYjO GdCfXeI GdYQHjI hCUHM GdTQb GdChSW Ydi CYJGH NGQWI LOjOI fJjLI JONd bhi OhdjI aj Jdc GdCMOGK, aYOJ JQcjG GdCeQ JgOjOkG UQjMkG ddCef Gdbhej hGMJeGd gjefI bhI efGaSI Ydi GdefWbI(B. (3Ef GdeJGHY Gdjhe dGSJQGJjLjI JQcjG aj Xd YgO GdQFjS (B((3CQOhZGf(B) (3jdGMX GdJWhQ GdMGUd aj GdbOQGJ GdOaGYjI HeNJda GdeSJhjGJ HeG jfGSH eUGdM hfahP JQcjG GdPj jLYd efgG OhdI eMhQ aj efWbI GdTQb GdChSW(B.s
Keywords: (3CQOhZGf, QLH WjH (B- (3GdCef Gdbhej (B- (3JQcjGs; (3GdSjGSI GdNGQLjI (B- (3JQcjG(B- (3GdbQf (B21s